Dilalah Ahwal al-Jumlah fi Surah al-Nisa’ - Khudair, Qosim Fakhir (Dzil Majaz: Journal of Arabic Literature, 2024)
The researcher chose Surat al-Nisa in an effort to highlight the semantic aspects in this surah, especially in the topic of news and creation. Its topics, as the researcher derives from whatever he wants, the researcher stopped in this research on a huge number of sources that help the seeker of knowledge to accomplish his research work, especially interpretations, books of Qur’an sciences, and books on the science of meanings, and we must point out that the interpretation of liberation and enlightenment had the upper hand in accomplishing this search. After completing this enjoyable work in which we toured the breadth of the blessed Surat An-Nisa, we concluded that Surat An-Nisa is one of the surahs that can be a fertile field for various types of semantic and interpretive studies due to the various topics it contains, especially inheritance, the rulings on what is permissible and forbidden, and acts of worship. The researcher found that in front of him is a rich sea of Wherever he wants